The Ethos Of Civil Technology Hands-On Assessments In The Revised Curriculum Assessment Policy Statement: A Discipline-Specific Pedagogy (Journal of Namibian Studies : History Politics Culture, 2024)
A discipline-specific pedagogy is crucial for teachers to cope with the recent curriculum reform in the Civil technology subject. Teachers need such a pedagogy to adequately plan, teach and assess self-made practical activities. The purpose of this study was to explore the ethos of Civil Technology hands-on assessments in the revised Curriculum Assessment Policy Statement through a Discipline-Specific Pedagogy lens. This study conveniently sampled seven Civil Technology teachers in woodwork, construction, and civil services. Document analysis and classroom observations were used to collect data and thematic analysis was used to analyse data. A discipline-specific pedagogy was used as a guide to this study. This study revealed that at face value, teachers could plan Practical Assessment Task lessons, however, their plans had no objectives clearly stating the expectations on the end product and teaching methods. These loopholes in planning knowledge were also manifested in the teaching knowledge where most teachers were not actively involved when learners were busy with their hands-on assessments.  This study recommends that thorough guidance is still needed for teachers to become fully autonomous in planning, teaching, and assessing activities. A more classroom-based, pedagogically sound training and community of practice approach is required for all technology teachers to bring flesh into the revised curriculum.